Produção de goma xantana a partir de casca de coco, soro de leite e casca de batata e suas misturas - Nascimento, Amanda Isabelly Leite Figueiredo (2017)
Xanthan gum is the microbial polysaccharide synthesized by bacteria of the genus Xanthomonas and considered the biopolymer of major commercial importance these days. Highlighted mainly due to its ability to form viscous and stable solutions, even in low concentrations, over a wide range of temperature and pH. It has expressive use in several industrial segments. The high cost of xanthan gum production is due to the substrate used and many researches have investigated new sources of carbon from agro-industrial waste. In addition to minimizing production costs, the use of alternative carbon sources leads to a reduction in the environmental impacts caused by these activities. The objective of this work was the production of xanthan gum in media based on agroindustrial residues: whey, coconut husk and potato peel and their mixtures: whey + coconut husk, whey + potato peel, peel of potato + coconut shell. Agroindustrial wastes of high biological value, easy to obtain and high availability, often discarded in an inadequate way. This disposal, besides bringing damages to nature corresponds to the waste of products with good nutritional characteristics, being potential substrates for the production of biopolymers. The study of the production from mixtures aims to evaluate if the addition of different carbon sources improves the productivity and / or quality of the gum obtained, or if production plants from agroindustrial residues should operate with only one of these residues. The fermentation process was carried out in an orbital shaker at 200 rpm using 250 mL Erlenmeyers containing 60 mL of fermentation medium supplemented with 0.01% (w/v) urea and 0.1% (w/v) phosphate of potassium. An experimental planning of mixtures, of the simplex-lattice type, was carried out, varying the composition of the fermentative media. All assays were performed at 28° C, in duplicate, for a period of 72 h. For analysis of the apparent viscosity of the xanthan gum produced, aqueous solutions were prepared in 1% (w/v) concentration for all fermentation assays. In this step the Brookfield digital viscometer coupled to the Rheocalc software was used. The highest productivity among the tests was obtained using the whey as a fermentation substrate. However, the obtained gum showed no characteristic pseudoplastic behavior, even after studies of nutritional composition adequacy. The best rheological grade gum was obtained from the coconut shell, with a value of 291cP at 25 s -1 of shear rate. It was observed that the coconut shell and potato peel mixture increased the rheological quality of the gum compared to that obtained when using only the potato peel as a fermentative substrate.